An exploration of prenatal breastfeeding self-efficacy: a scoping review - Liz M. McGovern; Laura O'Toole; Rachel A. Laws; Timothy C. Skinner; Fionnuala M. McAuliffe; Sharleen L. O'Reilly (BMC, 2024)
Abstract Background Breastfeeding self-efficacy is a woman's self-belief and confidence in her perceived ability to breastfeed. This modifiable determinant is strongly associated with breastfeeding initiation, exclusivity, and duration. It is unclear how important the timing of breastfeeding self-efficacy measurement and interventions are. The prenatal period appears underexplored in the literature and yet a prenatal focus provides increased opportunity for breastfeeding self-efficacy enhancement and further potential improvement in breastfeeding outcomes. This scoping review aims to synthesise the evidence on prenatal breastfeeding self-efficacy, describing for the first time the theoretical frameworks, measurement tools, and interventions used in the prenatal period. Methods 8 databases were searched using the PCC framework (Problem: breastfeeding, Concept: self-efficacy, Context: prenatal period). From 4,667 citations and 156 additional sources identified through grey literature and snowballing, data were extracted from 184 studies and 2 guidance documents. All were summarised descriptively and narratively. Results Just over half (57%) of included studies stated their theoretical underpinning, with Bandura's Self-Efficacy Theory / Dennis' Breastfeeding Self-Efficacy Framework predominant. Only half of intervention studies incorporated theory in their design. More intervention studies were undertaken in the past decade than previously, but the level of theoretical underpinning has not improved. Prenatal interventions incorporating theory-led design and using components addressing the breadth of theory, more frequently reported improving breastfeeding self-efficacy and breastfeeding outcomes than those not theory-led. Intervention components used less frequently were vicarious or kinaesthetic learning (52.5%) and involvement of social circle support (26%). The Breastfeeding Self-Efficacy Scales were the most common measurement tool, despite being designed for postpartum use. Overall, issues were identified with the late prenatal timing of breastfeeding self-efficacy investigation and the design, content and phraseology of measurements and interventions used in the prenatal period. Conclusion This review provides novel insights for consideration in the design and conduct of breastfeeding self-efficacy studies in the prenatal period. Future research should aim to be theory-led, commence earlier in pregnancy, and embed the breadth of self-efficacy theory into the design of interventions and measurement tools. This would provide more robust data on prenatal breastfeeding self-efficacy's role in impacting breastfeeding outcomes.